In praise of subgenera: taxonomic status of cobras of the genus Naja Laurenti (Serpentes: Elapidae) - Wallach, Van; Wüster, Wolfgang; Broadley, Donald G. (Zootaxa, 2009)
The genus Naja Laurenti, 1768, is partitioned into four subgenera. The typical form is restricted to 11 Asian species. The name Uraeus Wagler, 1830, is revived for a group of four non-spitting cobras inhabiting savannas and open formations of Africa and Arabia, while Boulengerina Dollo, 1886, is applied to four non-spitting African species of forest cobras, including terrestrial, aquatic and semi-fossorial forms. A new subgenus is erected for seven species of African spitting cobras. We recommend the subgenus rank as a way of maximising the phylogenetic information content of classifications while retaining nomenclatural stability.